Harmonic analysis in electrical system at Andalas University Hospital. (August 2019) - Afni, N; Nazir, R; Waldi, E P; Pawawoi, A
Abstract: In this paper, harmonic distortion in the electrical system at Andalas University Hospital is analyzed. The Total harmonic distortion (THD) was measured by The Fluke 430-II power analyzer for three days from 27 th - 29 th June 2018. The data were recorded every ten minutes. The THD of the current was from 3.09 % on Thursday at 08.40 (in phase L3) to 9.35 % on Thursday at 23.00 (in phase L1). The values of the THD show that high values of the THD occur at night from 18.00 to 08.00 at morning. The low values for the harmonic distortion of the installation occur during the day from 08.00 to 18.00 that occur for low active power. The harmonic distortion in the electrical system during the day was quite low. The current harmonic distortion was depending on the type of load. The non-sinusoidal current has harmonic content that interacts with the electrical system will create voltage distortion in the electrical system even if the supply is sinusoidal.